Oxygen‐Vacancy‐Mediated Photocatalysis over Bi2Sn2O7: Exceptional Catalytic Activity and Selectivity. Issue 24 (15th May 2019) - Huang, Shushu; Kou, Xin; He, Dan; Du, Chunfang; Wang, Xiaojing; Su, Yiguo
Abstract: A series of Bi2 Sn2 O7 photocatalysts was developed with the aim to regulate defect chemistry as well as electronic structure by modulating the charge states of tin species for boosting photocatalytic selective oxidation of alcohols performance. Defective centers, such as oxygen vacancies (OVs), were beneficial to enhancing the adsorption and activation of molecular oxygen. Meanwhile, the valence band edge potential of Bi2 Sn2 O7 with higher OVs content exhibited a distinct downshift, improving the thermodynamical driving force of photooxidation. Additionally, OVs contributed to promoting the separation efficiency of photogenerated carriers, which can be confirmed by the surface photovoltage measurement. By optimizing the electronic structure as well as defect chemistry, the optimal benzyl alcohol conversion efficiency was 76.0 % with selectivity toward benzaldehyde being about 100 %. It's found that photogenerated holes and . O2 − active species played critical role in photocatalytic aerobic oxidation. This work may provide a novel insight to clarify the role of defect chemistry during the selective benzyl alcohol oxidation over Bi2 Sn2 O7 photocatalyst. Abstract : The sun smiles : A series of Bi2 Sn2 O7 photocatalysts was developed with the aim to regulate defect chemistry as well as electronic structure by modulating the charge states of tin species for boosting photocatalytic selective oxidation of alcohols performance. Photocatalytic benzyl alcohol activity of Bi2 Sn2 O7 was originated from its higher Sn(II) content and the subsequent higher oxygen vacancies content, leading to the improvement of oxidizing ability, O2 adsorption on the surface and the photogenerated charges separation efficiency.